Gender, violence and social norms in Turkish psychological dramas - Nirun, Yasemin Bahloul. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
TV series have been an important part of the Turkish economy for the last two decades. Following the COVID-19 pandemic, the psychological dramas suddenly took over the television. The psychiatrist, writer and producer Gülseren Budayıcıoğlu produced four TV series based on her own books, in which she wrote about the lives of her patients. One of these series, named the Red Room (Kırmızı Oda), is a drama that is filmed in a psychiatry room that is almost an exact replica of Gülseren Budayıcıoğlu’s therapy room. The series became an extreme success story due to its high ratings and viewing records. The production team claims that their mission is to stop the violence with this carefully structured show, which also received appreciation and support from the government institutions. This thesis does not focus on the psychological reasons behind the increased attention of the audience; instead it aims to analyze the sociological and political positioning of the popular dramas within the dynamics of the current Turkish media. Considering the amount of influence and power that the current government has on the structure of the Turkish media, the strong ideologies embedded in the series towards gender, violence, society, mental illness and most importantly the protection of the family, are far from coincidental. This thesis aims to analyze the social codes that are embedded and portrayed in the Red Room based on gender, violence and family to further understand the presentation of the ideologies in power through the current media in Turkey.
Keywords: COVID-19 (Disease) -- Turkey.; Television series -- Psychological aspects.